UNDERSTANDING GENERATION Z"™S ENTREPRENEURIAL INTENTION AND BEHAVIOR: EVIDENCE FROM INDONESIA - Mustari, Mustari; Ramadhani, Fildza Anisya; Hasan, Muhammad; Inanna, Inanna; Supatminingsih, Tuti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
An important issue for entrepreneurship today is to increase the entrepreneurial intention of a country"™s productive age groups, including Generation Z. This research seeks to explore key components of the Theory of Planned Behavior (TPB) (attitude, subjective norms, and perceived behavioral control) to explain the entrepreneurial intention and behavior of Generation Z in Indonesia. This study employed a quantitative method. The data was collected through a questionnaire distributed using a purposive sampling technique, and a total of 713 respondents were participated in this study. Partial Least Squares "“ Structural Equation Modeling (PLS-SEM) was utilized to analyze the data. The results confirm that the TPB can predict the entrepreneurial intention and behavior of Generation Z in Indonesia, demonstrating that the attitude, subjective norms, and perceived behavioral control all have a positive influence on the entrepreneurial intention, as do the attitude and perceived behavioral control on the entrepreneurial behavior. Further, entrepreneurial intention has been shown to mediate the positive relationship between attitude, perceived behavioral control, and entrepreneurial behavior among Generation Z in Indonesia.JEL: E24, E220, I25, I140.